Respon Pertumbuhan Vegetatif Tanaman Cabai Merah Terhadap Berbagai Konsentrasi Garam Pada Inceptisol Jatinangor - Ibnu Rizki Perdana; Mieke Rochimi S; Pujawati Suryatmana (Composite : Jurnal Ilmu Pertanian, 2021)
Chili (Capsicum annum L) was one of the vegetable commodities that have a significant economic value. Farmland narrowed due to land conversion led to a shift of fertile agricultural lands into marginal lands such as saline land. This research aimed to determine respond of chili plant growth to salinity stress in Inceptisols. The experiment was conducted in August-October 2020 with located at Ciparanje Experimental field of Faculty of Agriculture, Padjadjaran University, Jatinangor District, Sumedang Regency. This research used randomized block design using four level treatment of NaCl concentration: 0 dS/m (a0), 2 dS/m (a1), 4 dS/m (a2), and 6 dS/m (a3). The result showed that there was no significant between treatment soil salinization of plant growth parameters like plant height and shoot root ratio but significant of number of leaves at 7 day after plant and canopy width at 28 day after plant on treatment salinization 6 dS/m.